2022
DOI: 10.15587/1729-4061.2022.257600
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization of bioethanol-gasoline fuel blends for development combustion energy and reducing exhaust gas emissions

Abstract: The effect of the magnetization field on molecular interactions of the bioethanol-gasoline fuel blends was investigated. This technique was promoted to escalate both the increase in combustion energy and reduce emissions in the internal combustion engine. The bioethanol and gasoline fuel are used for the single-cylinder four-stroke engine with different mixtures, namely E0, E10, E20, and E30, serially. Distinguish of electromagnetic field strength with various intensity was given into the fuel by lower than 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Research has indicated that magnetic field induction affects the characteristics of pre-mixed ethanol combustion flames, resulting in more effective and efficient flames [97]. Moreover, magnetization of bioethanol-gasoline fuel blends has been demonstrated to increase combustion energy in internal combustion engines, reduce emissions, and enhance combustion quality [98].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%
“…Research has indicated that magnetic field induction affects the characteristics of pre-mixed ethanol combustion flames, resulting in more effective and efficient flames [97]. Moreover, magnetization of bioethanol-gasoline fuel blends has been demonstrated to increase combustion energy in internal combustion engines, reduce emissions, and enhance combustion quality [98].…”
Section: Potential Applications Of Magnetic Field To Combustionmentioning
confidence: 99%